METHODS FOR THE BIOCONVERSION OF MINERAL FERTILIZERS INTO GREEN FODDER ON A PEAT BOG - Tatiana Yuryevna ANISIMOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article presents the results of the fifth year of research in a two-factor field experiments, all variants were compared with absolute control without overseeding and fertilizer application. The agroeconomic and agro-energy efficiency of the use of the studied agricultural practices has been determined. An analysis of the agroeconomic and energy assessment showed that the combination of the use of direct sowing and fertilizers over five years of observation and research (from 2017 to 2021) was effective and contributed to a reduction in the cost of 100 feed unit ha-1 by an average of 41-46%; obtaining the greatest profit – 376-826 $ ha-1. The highest payback of a feed unit of 1 kg of NPK was also noted in variants with a cultivated phytocenosis, this indicator increased by 1.2-1.6 times compared to the natural phytocenosis. It was found that the use of overseeding against the background of NPK increased the energy efficiency from 1.6-2.0 to 2.9-3.4. Therefore, taking into account the recoupment of energy costs, we can conclude that N60P90K120 and both doses of NPK in a cultivated phytocenosis can be considered energetically optimal doses of fertilizers in a natural phytocenosis.